Revisiting Financial Behavior in Traditional Market Traders: The Hidden Role of Self-Control - Muhammad Saleh; Ilham Safar (JURNAL DIMENSI, 2026)
This study investigates the role of financial literacy, financial attitude, and self-control in shaping the financial behavior of traditional market traders at Lakessi Market, Pare-pare City, Indonesia. The study addresses a research gap in the financial behavior literature, particularly the limited empirical evidence on self-control as a mediating variable among traditional market traders in Eastern Indonesia. The objective of this research is to examine both the direct and indirect effects of financial literacy and financial attitude on financial behavior through self-control. This study employed a quantitative causal-associative design using a survey method. Data were collected from 286 traders selected through proportionate stratified random sampling from a population of 1,000 traders. Hypotheses were tested using PROCESS Macro Model 4 with 5,000 bootstrap samples in IBM SPSS Statistics 29. Results indicate that financial literacy and financial attitude exert significant positive direct effects on both financial behavior (β = 0.564; β = 0.531) and self-control (β = 0.406; β = 0.388), while self-control significantly influences financial behavior (β = 0.313). Bootstrap mediation analysis confirms partial mediation on both pathways: the indirect effect of financial literacy through self-control is 0.127 (95% CI [0.072, 0.187]) and that of financial attitude is 0.142 (95% CI [0.085, 0.203]). Self-control functions as a complementary mediating bridge rather than a primary pathway. A threshold effect is identified whereby moderate financial literacy suffices to produce meaningful behavioral change. These findings provide evidence-based guidance for policymakers and market authorities to design interventions combining financial literacy training with structural supports for informal economy traders.